PENDAMPINGAN HEALTH MANAGEMENT BERBASIS APLIKASI SEBAGAI MEDIA SELF-MANAGEMENT PENDERITA HIPERTENSI DI WILAYAH RW 07 KELURAHAN KAPASAN KECAMATAN SIMOKERTO SURABAYA - Susanti, Susanti; Kristiani, Rina Budi; Yobel, Sosilo; Bistara, Difran Nobel (Community Development in Health Journal, 2023)
Introduction & Aim: Patients with hypertension have a tendency not to self-management of their disease. The method that can be used to improve self-management is to utilize existing digital technologies such as smartphone-based mobile health. This community service aims to improve the self-management of hypertension patients. Method of Activity: Implementation of assistance in the application of health management applications with a frequency of 3 times for 3 weeks. To measure the success of the activity, pre-test and post-tests were carried out which included data on the knowledge of hypertension patients in carrying out self-management. Data were presented descriptively to analyze the effectiveness of activities. Results: The intervention in providing education and assistance in using the application showed that most of the respondents had understood smartphone applications as a media for self-management. This was evidenced by the fact that the knowledge of the respondents increased from the beginning, the knowledge of the respondents was lacking by 17 people (51.52%) then became 18 people (54.55). %) with good knowledge. Discussion: The assistance implementation of application health management is to improve the knowledge of respondents regarding self-management to control his health effectively. Self-management in hypertension patients is the application of the DASH diet, blood pressure control, physical activity, and drug consumption. This intervention can provide motivation for people with hypertension to be able to do self-management in order to improve self-efficacy & quality of life.